2006
DOI: 10.1523/jneurosci.1312-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Contributions to Human Brain Morphology and Intelligence

Abstract: Variation in gray matter (GM) and white matter (WM) volume of the adult human brain is primarily genetically determined. Moreover, total brain volume is positively correlated with general intelligence, and both share a common genetic origin. However, although genetic effects on morphology of specific GM areas in the brain have been studied, the heritability of focal WM is unknown. Similarly, it is unresolved whether there is a common genetic origin of focal GM and WM structures with intelligence. We explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
205
5
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(243 citation statements)
references
References 46 publications
30
205
5
3
Order By: Relevance
“…Specifically, small heritability values (<40%) were found for the right hippocampus and thalamus, and left amygdala, hippocampus, and caudate, but moderate values (40-60%) were found for the right amygdala and left thalamus. Our estimates for heritability were lower than those previously reported for the amygdala (e.g., 55-71% for right amygdala in Hulshoff et al, 2006;Kremen et al, 2010;and Wright et al, 2002, vs. 48% reported here) and for the hippocampus (e.g., 64-71% for right hippocampus in Kremen et al, 2010, andWright et al, 2002, vs. 34% reported here), but higher for others such as the thalamus (e.g., 0% in Wright et al, 2002 vs. 58% for left thalamus reported here).…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, small heritability values (<40%) were found for the right hippocampus and thalamus, and left amygdala, hippocampus, and caudate, but moderate values (40-60%) were found for the right amygdala and left thalamus. Our estimates for heritability were lower than those previously reported for the amygdala (e.g., 55-71% for right amygdala in Hulshoff et al, 2006;Kremen et al, 2010;and Wright et al, 2002, vs. 48% reported here) and for the hippocampus (e.g., 64-71% for right hippocampus in Kremen et al, 2010, andWright et al, 2002, vs. 34% reported here), but higher for others such as the thalamus (e.g., 0% in Wright et al, 2002 vs. 58% for left thalamus reported here).…”
Section: Discussioncontrasting
confidence: 99%
“…This association is mediated by genes shared between structural brain measures and full scale IQ in adulthood (Hulshoff Pol et al, 2006;Posthuma et al, 2002). In our pediatric twin cohort we demonstrated that this genetic association between brain structure and IQ is already present at a young age.…”
Section: Brain Structure and Cognitionsupporting
confidence: 52%
“…A study involving 54 monozygotic (MZ) and 58 dizygotic (DZ) twin pairs, and 34 of their siblings, estimated heritabilities for focal GM and WM areas of the brain using a VBM approach (Hulshoff Pol et al, 2006). Hemispheric differences in proportional genetic contributions were found for High bilateral genetic correlations between structural homologues were found, suggesting that inter-hemispheric covariance is largely genetically mediated.…”
Section: Genetics and Twin Studiesmentioning
confidence: 99%